2009
DOI: 10.1111/j.1743-6109.2009.01460.x
|View full text |Cite
|
Sign up to set email alerts
|

The Place of Female Sexual Dysfunction in the Urological Practice: Results of a Dutch Survey

Abstract: Introduction Female sexual dysfunction (FSD) is a highly prevalent and often underestimated problem. There is a strong association between urological complaints and FSD. Aims The purpose of this survey was to evaluate how Dutch urologists address FSD in their daily practice. Methods We performed an anonymous survey study. A 17-item anonymous questionnaire was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 43 publications
1
23
2
Order By: Relevance
“…Similarly, in a recent survey among urologists, 6% stated they ask each female patient about SF. Yet, a much larger group (87%) stated that they ask about SF if a patient presents with specific complaints, such as lower abdominal pain, urinary or faecal incontinence, urgency or frequency 7. Comparable studies carried out by members of the British Society of Urogynaecology and the American Urogynaecologic Society, with respect to female sexual dysfunction, showed that 50% of the British urologists and gynaecologists screened for female sexual dysfunction compared with 77% of the American members 6 7 21.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in a recent survey among urologists, 6% stated they ask each female patient about SF. Yet, a much larger group (87%) stated that they ask about SF if a patient presents with specific complaints, such as lower abdominal pain, urinary or faecal incontinence, urgency or frequency 7. Comparable studies carried out by members of the British Society of Urogynaecology and the American Urogynaecologic Society, with respect to female sexual dysfunction, showed that 50% of the British urologists and gynaecologists screened for female sexual dysfunction compared with 77% of the American members 6 7 21.…”
Section: Discussionmentioning
confidence: 99%
“…Gynaecologists are alert to pelvic floor tissue-stretching and pudendal nerve damage during vaginal delivery, and are aware that traumatic damage can cause faecal and urinary incontinence 5 6. Many urologists screen for sexual dysfunction as well 7. Gastroenterologists are confronted with the posterior pelvic floor compartment disorders.…”
Section: Introductionmentioning
confidence: 99%
“…This could partly be explained by the fact that postal surveys are well known for low-response rates as it has been demonstrated in many other postal surveys published in the literature [21]. The use of email surveys or even direct telephone conversations could be used to improve the response rates.…”
Section: Discussionmentioning
confidence: 96%
“…However, the routine identification of FSD is still lacking (25). Surgery for prolapse and urinary incontinence does not necessarily ensure optimal sexual function, and conflicting results have been reported (13-16).…”
Section: Discussionmentioning
confidence: 99%